O México como aliado dos EUA no projeto de integração das Américas - Santos, Marcelo [UNESP] (Instituto Brasileiro de Relações Internacionais, 2007)
O artigo sugere que, nas duas últimas décadas, os governos mexicanos vêm adotando medidas políticas e econômicas amplamente afinadas com o modelo de integração econômica das Américas proposto pelos EUA. A adesão incondicional ao Nafta e o empenho para consolidar os projetos do Corredor Biológico Mesoamericano e do Plano Puebla-Panamá são exemplos fundamentais dessa estratégia.

The article suggests that, during the two last decades, the Mexican government has been adopting political and economic measures in tune with the economic integration model for the Americas proposed by the United States of America. Examples of this strategy are the unrestricted entry into North-American Free Trade Agreement (Nafta) and the effort to consolidate the projects for a Mesoamerican Biological Corridor and the Puebla-Panamá Plan.
Mexico as an ally to the United States in the project for integration of the Americas
Keywords: EUA; México; Integração econômica; USA; Mexico; Economic union